Hermeneutika Al Quran Tafsir Al-Azhar (Analisi Hermeneutis Ayat-ayat Akidah dan Ibadah) - pathur rahman (Medina-te : Jurnal Studi Islam, 2018)
Hamka's interpretation of al-Azhar in his interpretation clearly reveals the operational-functional hermeneutics of the Qur'an, although methodologically it is not as a whole and synergistic in representing the Qur'an's hermeneutics as a method of interpretation. "Taslim" referred to by Hamka in the direction of al-Azhar's interpretation of aqidah and worship is the statement of faith and worship not on the understanding and spirit of the verse. The non-use of the term hermeneutics in al-Azhar's interpretation does not require the absence of hermeneutical or operational-functional ideas in the study of the Qur'an. Therefore, efforts to make contextualization of the Qur'an, as initiated by hermeneutics when dealing with text in embodying the meaning of the Qur'anic sholihun likulli era wa makan as a Christian solution, to further earth the al-Qur'an has long been done.